Cetuximab in preoperative treatment of rectal cancer - term outcome of the XERT trial - Velenik, Vaneja (Radiology and oncology (Ljubljana), 2012)
Preoperative capecitabine-based chemoradiotherapy (CRT) is feasible for the treatment of resectable locally advanced rectal cancer (LARC). To try to improve efficacy, we conducted a phase II studz in which the epidermal growth factor receptor-targeting monoclonal antibody cetuximab was added to capecitabine-based CRT. The results for long-term survival and for an analysis investigating the relationship between survival and patient and disease characteristics, including tumour KRAS mutation status, and surgery type, are presented. Patients with resectable LARC received capecitabine (1250mg/m2 twice daily, orally) for 2 weeks followed by cetuximab alone (400 mg/m2 for 1 week) and then with CRT (250 mg/m2/week) comprising capecitabine (825 mg/m2 twice daily) and radiotherapy to the small pelvis (45 Gz in 25 1.8-Gz fractions), five dazs a week for five weeks. Surgery was conducted six weeks following CRT, with post-operative chemotherapy with capecitabine (1250 mg/m2 twice daily for 14 days every 21 days) three weeks later. Forty-seven patients were enrolled and 37 underwent treatment. Twenty-eight of the patients (75.7%) had T3N+ disease. Thirty-six patients were evaluable for efficacy. The median follow-up time was 39.0 months (range 5.0-87.0). The three-year local control, disease-free survival, relapse-free survival and overall survival rates were 96.9% (95% CI 90.0-100), 72.2% (57.5-86.9), 74.3% (95% CI 59.8-88.8) and 68.1% (95% CI 36.7-99.4), respectively. There was no significant association between survival and gender, age, tumour location in the rectum, type of surgery, pathological T or N status, tumour regression grade or tumour KRAS mutation status, although sample sizes were small. Preoperative cetuximab plus capecitabine-based CRT was feasible in patients with resectable LARC and was associated with an impressive three-year local control rate. The use of tumour KRAS mutation status as a biomarker for the efficacy of cetuximab-based regimens in this setting requires further investigation.
Keywords: Antibodies, monoclonal; bolniki; danka; Drug therapy; Genes, RAS; mutacije; Mutation; novotvorbe; preživetje; radioterapija; Radiotherapy; Receptor, epidermal growth factor; Rectal neoplasms; Survival analysis; tumor